LANDASAN PERUMUSAN LOCUS DELICTI DALAM SURAT DAKWAAN PADA KEJAHATAN SIBER - Pakaya, Rio Dirgantara; Mahyani, Ahmad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This research will discuss the basis for the formulation of locus delicti in an indictment on cybercrime, an indictment is an essential matter in a criminal procedure, especially if it contains material conditions, which if these conditions are not met can result in the indictment being blurred (Obscuur Libel) or null and void (for the sake of law). Vernietigbaar). The mistake in formulating locus delicti was the beginning of the non-fulfillment of the requirements in the indictment. So that the formulation of the problem is whether the basis for theformulation of locus delicti in the indictment on cybercrime has been regulated in procedural law in Indonesia. This type of research is a legal research by studying the existing positive legal rules and adding conceptually exploring the issues discussed through legal principles and expert opinions. So it is found that in criminal procedural law in Indonesia there are no rules that regulate explicitly and are used as a basis in formulating locus delicti in an indictment on cybercrime